Aging-induced degradation in tracking performance in three-dimensional movement - Hyeonseok Kim; Shinsuke Tobisawa; Hyungwon Park; Jaehyo Kim; Jongho Lee; Duk Shin (SICE Journal of Control, Measurement, and System Integration, 2024)
Unlike ballistic movements such as reaching, little is known about how aging affects tracking performance. The current study initially aimed at confirming the differences in tracking performance between younger and older people. The experiment included 14 young and 10 older subjects who were instructed to perform a circular tracking task on the fronto-parallel and sagittal planes with a visible target in the first half interval (called the feedback (FB) interval) and an invisible target disappearing and reappearing in the remaining interval (called the feedforward (FF) interval). The results demonstrated that the aging effect was sufficient to deteriorate tracking performance, regardless of the environment. However, the older group’s performance was not significantly influenced by the depth movement, whereas the younger group’s performance significantly deteriorated during the FB interval. Finally, the differences in errors between the FF and FB intervals for each movement plane were investigated, demonstrating the vulnerability of the internal model used for each plane to the visibility of the target. The younger group demonstrated a significant difference between the fronto-parallel and sagittal planes; however, the older group exhibited no significant difference, indicating that the younger group acquired an internal model sensitive to visual information. We confirmed aging-induced tracking performance degradation and highlighted the impact of aging on tracking performance, resulting in an increased understanding of cerebellar motor control rather than conventional ballistic movements.